(untitled) (Bioscience Journal, 2019)
The growing in shaded systems is one of the strategies adopted to mitigate the impacts of climate change on coffee trees. However, there are few studies about the effect of shading on the growth and production of clones of robusta coffee (Coffea canephora). Besides that, exist a paradigm in Brazil of that the shading in coffee robusta is synonymous of less yield. Thus, the aim of this work was to evaluate whether C. canephora genotypes subjected to shading increase their yield and growth vegetative under field conditions. The study was performed between September 2013 and July 2017 (four harvests) in Alegre, Espírito Santo state, Brazil. Three genotypes of cultivar Conilon Vitória - Incaper 8142 were evaluated (03V, 06V, and 12V) and four levels of shade: full sunlight (witness) and, low, moderate and, high shade, with 38, 48 and, 68% of real capacity of shade, respectively. The shade was performed using black polyolefin screens; plants growing in full sunlight were only fenced. The tested shade levels affected the growth rate and yield of Robusta coffee plants. The shading caused a greater leaf expansion as compared to the full sunlight, as well as greater etiolation of the plagiotropic and orthotropic branches. The genotype 06V was shown to be responsive to shading, with a statistically equal production independently of shade level. The low, moderate, and high shade levels affected negatively the yield of genotypes 03V and 12V. The shading can improve the yield of Robusta coffee, in this case, of the genotype 06V of the cultivar Conilon Vitória - Incaper 8142. The success of shaded plantations depends the choice of the shade responsive genotypes and appropriate shading level.